OPTIMALISASI INPUT PRODUKSI UBI JALAR DI KAMPUNG WEBI DISTRIK RASIEI KABUPATEN TELUK WONDAMA - Uce Esmeralda Lutlutur; Deasi Mayawati; Sejati, Satrio (Sosio Agri Papua, 2023)
This research aims to determine the optimal use of production factors such as land area, labor and costs to increase the quantity of sweet potato production. This research was conducted in Kampung Webi using 30 sample farmers. Data were analyzed using Cobb-Douglas multiple regression then continued using SPSS. The results of the research concluded that together these factors influence sweet potato production, and these factors are able to explain sweet potato production of 17.57kg/season. Partially, the production factors that have a real influence are land area and cost of sweet potatoes. one food crop as a substitute for the staple food (rice). Sweet potatoes can grow both in the lowlands and in the mountains with a temperature of 270c and a light period of 11-12 hours per day (Soemartono, 1984). According to the Big Indonesian Dictionary (Depdikbud: 1995: 628) optimization comes from the basic word optimal which means best and highest. So optimization is a process of improving or improving. Hysocc, (2014) said that optimization is a process to achieve ideal results or optimization (the effective value that can be achieved). According to Sofyan, (2015) production is all activities in creating and increasing the utility of goods and services, for activities where production factors are needed in economics in the form of land, labor and skills (organizational, managerial and skills).